Effect of Antioxidant Extract from Cherries on Diabetes - Lachin, Tahsini (Recent Patents on Endocrine, Metabolic & Immune Drug Discovery (Discontinued), 2014)
Diabetes is a chronic metabolic disorder in humans constituting a major health concern today whose prevalence has continuously increased worldwide over the past few decades. Production of reactive oxygen species (ROS) and disturbed capacity of antioxidant defense in diabetic subjects have been reported. It has been suggested that enhanced production of free radicals and oxidative stress is the central event for the development of diabetic complications. Antioxidants can play an important role in the improvement of diabetes. There are many reports on the effects of antioxidants in the management of diabetes. This study aimed at evaluating the effect of antioxidant extract and purified sweet and sour Cherries on hyperglycemia, microalbumin and creatinine level in alloxan-induced diabetic rats. Thirty six adult Male Wistar rats were divided equally into six groups. Diabetes was induced in the rats by an intraperitoneal injection with 120 mg/kg body weight of alloxan. Oral administration of cherry extract at a concentration of 200 mg/kg body weight for 30 days significantly reduced the levels of blood glucose, and urinary microalbumin. Also an increase in the creatinine secretion level in urine was observed in the diabetic rats treated with the cherry extract as compared to untreated diabetic rats. In this paper, the most recent patent on the identification and treatment of diabetes is used. In conclusion, cherry antioxidant extract proved to have a beneficial effect on the diabetic rats in this study. In light of these advantageous results, it is advisable to broaden the scale of use of sweet and sour cherries extract in a trial to alleviate the adverse effects of diabetes.
Keywords: diabetic rat